Multinational Tax Incentives and Offshored U.S. Jobs - Williams, Braden M. (The Accounting Review, 2018)
ABSTRACT This paper examines if, when, and to what extent multinational tax incentives incrementally explain where firms move offshored U.S. jobs. Using jobs data from a Department of Labor program called Trade Adjustment Assistance, I find a significant association between tax incentives and both the likelihood that a foreign country hosts offshored U.S. jobs and the number of U.S. jobs it hosts. This association is stronger when managers have discretion to coordinate cross-border transactions internally and when they do not face political costs imposed by labor unions. Following instances of offshoring, I find some evidence that offshoring firms have lower effective tax rates, but these reductions are concentrated within larger layoffs in which jobs are sent to low-tax countries. These findings are relevant to understanding the real effects and welfare consequences of incentives created by current U.S. tax policy. JEL Classifications: F23; H26; J63; L14.